2014
DOI: 10.3348/kjr.2014.15.5.637
|View full text |Cite
|
Sign up to set email alerts
|

Massive Thoracoabdominal Aortic Thrombosis in a Patient with Iatrogenic Cushing Syndrome

Abstract: Massive thoracoabdominal aortic thrombosis is a rare finding in patients with iatrogenic Cushing syndrome in the absence of any coagulation abnormality. It frequently represents an urgent surgical situation. We report the case of an 82-year-old woman with massive aortic thrombosis secondary to iatrogenic Cushing syndrome. A follow-up computed tomography scan showed a decreased amount of thrombus in the aorta after anticoagulation therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…She was diagnosed with acute mesenteric ischaemia and hepatic infarction. Kim et al 18 reported a case of thoracoabdominal aortic thrombosis in an 82-year-old woman with iatrogenic Cushing syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…She was diagnosed with acute mesenteric ischaemia and hepatic infarction. Kim et al 18 reported a case of thoracoabdominal aortic thrombosis in an 82-year-old woman with iatrogenic Cushing syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Floating thrombus was also described in the case of 82 year old patient with iatrogenic Cushing's disease (after treatment for RA). The pathomechanism leading to hypercoagulation in this case was probably the increased blood platelet and von Willebrand factor activity caused by glycocortycosteroids [1].…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess a thrombus in aorta the most optimal examination would be angio-CT usually preceded after the ultrasound examination [1,3]. In the case of FFT placed in the thoracic aorta the alternatives are MR, angio-MR and transesophageal echocardiography in the case of FFT placed in the thoracic aorta [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoraco-abdominal aortic thrombus leading to mesenteric ischemia is a rare presentation in the emergency department. Diagnosis requires a high index of suspicion especially in patients with risk factors, which include cardiac embolus related to arrhythmia or valvular heart disease, peripheral artery disease, vasoconstrictive medications, hemodialysis, hereditary or acquired thrombotic conditions, infections, and hypovolemia [ 2 ]. Delays in diagnosis and treatment of thrombi lead to high mortality [ 3 ].…”
Section: Introductionmentioning
confidence: 99%